ETHNOMEDICINAL PLANTS USED AGAINST COMMON DIGESTIVE PROBLEMS - Adnan, Muhammad; Bibi, Roqaia; Azizullah, Azizullah; Andaleeb, Rani; Mussarat, Sakina; Tariq, Akash; Ullah, Riaz; AbdElsalam, Naser M.; Khan, Abdul Latif; Begum, Shaheen (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Ethnomedicinal knowledge is highly significant for persistence of human health care. Different studies shown that medicinalplants are considered as curing agent for digestive disorders in Pakistan. The aim of present review is to explore this ethnomedicinal informationall over the Pakistan and to investigate the ecological status of these species in the country.Methodology: Online litera